The Ameliorating Effects of Salvia hispanica‎ Seeds Ethanolic Extract on ‎Methylprednisolone-Induced Osteoporosis in Female Rabbits - A Kadhem, Mariam; M AL-Rekabi, Falah; A Jassam, Samah (The Iraqi Journal of Veterinary Medicine, 2023)
This study aimed to determine the effect of an ethanolic extract of Salvia hispanica‎ (Sh) seeds on ‎osteoporosis induced by methylprednisolone (MP) in female rabbits by assessing the bone ‎mineral density (BMD), serum levels of calcium, phosphorus, vitamin D, and parathyroid ‎hormone, as well as histopathological changes in the femur bone. Fifty female rabbits ‎‎(Lepus cuniculus) averaging 1800±125 g and 8±1.4 months old were used in this study. ‎They were randomly allocated to five groups of 10 rabbits each. The negative control group ‎received only subcutaneous normal saline (1 mL/kg BW). The positive control group received MP subcutaneously at a dose of 0.2 mg/kg BW per ‎day for 30 days, followed by oral normal saline (1 mL/kg BW) per day for two months. ‎Group 3 received MP followed by oral administration of Sh seed ethanolic extract at a dose of 600 mg/kg BW per day for two months. Group 4 received MP followed by oral administration of alendronate (Ale) at a dose ‎of 3.6 mg/kg weekly for two months. Group 5 received MP ‎followed by Ale and then Sh seed ethanolic extract. The study continued until one ‎week after the cessation of the treatments. The results showed that the BMD and serum ‎concentrations of calcium, phosphorus, and vitamin D significantly decreased (P<0.05), ‎while serum concentrations of parathyroid hormone significantly increased (P<0.05) in the ‎positive control and alendronate groups compared with the negative control group after two ‎months of treatment and after one week of withdrawal. However, the administration of Sh methanolic extract to the animals in the three treatment groups ‎ameliorated these parameters and reverted them to normal values. Histopathological ‎analysis of the femur bone head revealed abnormal bone morphology in the positive control ‎group, while Sh extract treatment preserved the normal histology in the other ‎groups. These findings concluded to that Sh seeds ethanolic extract has the ‎potential to prevent bone loss induced by chronic glucocorticoid therapy and may have ‎significant implications for the treatment of osteoporosis.